Cochlear implantation in patient with Charcot-Marie-Tooth disease. Issue 2 (April 2021) - Kobayashi, Masumi; Yoshida, Tadao; Sugimoto, Satofumi; Teranishi, Masaaki; Hara, Daisuke; Kimata, Yukari; Sone, Michihiko
Abstract: Two patients with auditory neuropathy spectrum disorder (ANSD) considered to be associated with Charcot-Marie-Tooth (CMT) are reported. In case 1, a 23-year-old man presented with progressive bilateral sensorineural hearing loss (SNHL) from 10 years of age and was diagnosed with ANSD. He was later diagnosed with CMT by neurological testing. In case 2, a 16-year-old girl, the younger sister of the patient in case 1, presented with progressive SNHL with similar auditory findings since 6 years of age as those of her brother. Both cases underwent bilateral cochlear implantation. In case 1, the maximum discrimination score improved to 45% 24 months after the first side of cochlear implantation from 5% before the surgery. In case 2, the score was 5% 10 months after cochlear implant (CI) surgery from 0% before the surgery. CI treatment for CMT patients has been considered difficult because of both failure in synchronization of nerve conduction due to demyelination and axonal failure of the auditory nerve. Though slower progress compared to the average subset of patients receiving CI was seen, significant improvement was gradually observed in the present patients after bilateral cochlear implantations. CI is thus a viable option for rehabilitation of SNHL in CMT patients.